2020
DOI: 10.1111/inr.12573
|View full text |Cite
|
Sign up to set email alerts
|

Evidence into action: a policy brief exemplar supporting attainment of nursing now

Abstract: Aim To provide a framework for the production of policy briefs, and offer a practical example of how evidence can be turned into a succinct document to inform policy and bring about change targeted at delivering universal health coverage. Introduction Policymakers are too busy, or do not have the necessary expertise, to read and comprehend complex scientific papers. As a result, policy briefs that capture and present the essential points are needed if evidence‐informed policy is to be developed and implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Nursing as a profession is well positioned to impact the SDGs due to the reach of its influence and care, including those with the greatest health inequalities and from the most remote locations (Benton et al, 2020b). And yet, despite the recognition in existing literature, it appears that nursing may be falling short of its ability to impact the SDGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing as a profession is well positioned to impact the SDGs due to the reach of its influence and care, including those with the greatest health inequalities and from the most remote locations (Benton et al, 2020b). And yet, despite the recognition in existing literature, it appears that nursing may be falling short of its ability to impact the SDGs.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses have been identified as having a pivotal role to play in addressing the SDGs. They make a central contribution to achieving health priorities as a result of the large workforce, global presence, and far reach to remote areas, vulnerable populations, and minority groups (Benton, Watkins, Beasley, Ferguson, & Holloway, 2020b; World Health Organization [WHO], 2020).…”
mentioning
confidence: 99%
“…Furthermore, Dossey, et al (2019) (30) , Kitt-Lewis, et al (2020) (31) and Kurth (2017) (32) emphasized the importance of increasing awareness of the sustainable development goals (SDGs) within nursing in various categories of healthcare providers. In this aspect, Benton, et al (2020) (33) confirmed that the nursing profession is well-positioned to have an impact on the SDGs due to the reach of its influence and care, including those with the largest health disparities and from the most remote regions. While, Fields and Cunningham -Williams (2021) (34) demonstrated that nursing may be falling short of its capacity to impact the SDGs due to concerns of lacking sustainable consciousness, inadequate research on the SDGs, and shortages in the number and quality of nurses.…”
Section: Nurse Managers' Sustainable Management Behaviorsmentioning
confidence: 99%
“…These include (1) redesigning current services in acute care and community-based settings to promote nurse innovation and encourage nurses in leadership roles; (2) investing in all aspects of nursing practices and ensuring their involvement in health promotion and management across the lifespan; (3) advancing legislation and regulations to expand advanced practice authority and redefine scopes of practice to optimise nursing contributions; and (4) raising the profile and status of nurses at local and global levels. 12,82 Strengthen nursing leadership and ensure that nurses are well represented at all levels of decision-making and have a voice in influencing health and public policy. There is a pressing need to cultivate a critical mass of nurse leaders who are policy competent to enable them to engage in health policy and political discussions to improve health, ensure quality of service delivery, and reduce inequalities in health and contribute to stronger economies and communities.…”
Section: Joanne Bosanquet Mbe Chief Executive Officer Foundation Of Nursing Studiesmentioning
confidence: 99%